Podcast Program Management for Information Dissemination during Covid-19 Pandemic: A Study of SMAN 8 Yogyakarta - Maemunah (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This research aimed to study implementing and managing a podcast program, Podcat Pakci, as a medium for information dissemination amid the Covid-19 pandemic at SMAN 8 Yogyakarta. Design/methods/approach – The paper scrutinized the management process of the podcast program, which included planning, organizing, directing, and controlling activities, with teachers playing the roles of mentors and supervisors. The dissemination of the podcasts via platforms like Spotify and YouTube, in addition to social media promotions, was also examined. Findings – The research demonstrated how a student-led podcast served as an effective platform for spreading educational and cultural information. This initiative contributed to student engagement and skills development and ensured a broad outreach. Research implications/limitations – While the research underscores the potential of podcasts as student-led projects in educational settings during global crises, its focus on one specific school limits the generalizability of the findings. Future research should focus on exploring podcast programs across different educational contexts and investigating their long-term impacts on student development and learning outcomes. Practical implications – The findings serve as a model for other schools, illustrating how a podcast program can disseminate information, foster student engagement, and enhance skills, particularly during crises like a pandemic. Originality/value – This study uniquely focuses on using a podcast program in an educational setting during a global crisis, emphasizing the innovative and strategic use of media to maintain communication and learning engagement in challenging times.